Controlling Peri-Urban Agricultural Land Conversion Based on Economic Constitutional Principles for Food Security - Christenia Gladysthea Arvita Andries (Legtimacy: Journal of Law and Islamic Law, 2025)
This study examines the conversion of agricultural land in fringe areas and its severe threat to national food security across Indonesia. Despite the existence of the Sustainable Food Agricultural Land Protection Law, land conversion remains massive due to ineffective enforcement and rapid urban sprawl. Utilizing a normative juridical method with statutory and conceptual approaches, this research analyzes the integration of economic constitutional principles, specifically Article 33 of the 1945 Constitution, into existing land control regulations. The findings clearly indicate that current regulations fail to adequately balance economic development with essential agricultural preservation. To fully realize a welfare state, government policies must strictly regulate regional land conversion by applying sound economic and moral logic. Integrating these constitutional principles directly ensures sustainable land use, actively protects rural livelihoods, and absolutely guarantees public access to basic food needs. Strict law enforcement and community participation are highly vital for maintaining truly optimal social welfare.